Analysis of Location and Service Quality on Visitor Interest with Promotion Strategy as an Intervening Variable at the New Building of Pasar Raya Phase VII, Padang City - Hidayatul Putri Azizah; Azzahra Azzahra; Shania Vadhillaesa; Doni Guswandri Putra; Lusianas Lusianas (Green Publisher Indonesia, 2025)
Padang City Supermarket Phase VII is one of the traditional trading centers that has been revitalized to improve attractiveness, comfort, and service quality for visitors. However, low visitor numbers remain a challenge, so it is important to analyze locational factors, service quality, and promotional strategies and their influence on visitor interest. This study aims to examine the influence of location and service quality on visitor interest, with promotional strategies as intervening variables. The research used a quantitative approach by distributing questionnaires to 30 respondents who visited Phase VII Supermarket. Data analysis was carried out using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The study results show that service quality has a significant effect on visitor interest, while location has no direct effect. In addition, promotional strategies were shown to act as a mediating variable in the relationship between location and visitor interest, although they are not effective in mediating the influence of service quality. These findings confirm that improving service quality and implementing appropriate promotional strategies can strengthen visitor interest, while also providing input for market managers and local governments in formulating more effective market development policies. In conclusion, the success of traditional market revitalization depends not only on physical development but also on service quality and promotional strategies that can create a positive shopping experience for visitors.